A comparative analysis of hematopoietic stem cell transplantation in pediatric and adult patients: a systematic review and meta-analysis - Maurya, Shailendra Shanker; Sagar, Nitin; Chaturvedi, Sumit; Pandey, Maneesha; Kushwaha, Sapana; Kashyap, Rajesh (Frontiers in Transplantation, 2025)
IntroductionHematopoietic stem cell transplantation (HSCT) is a significant treatment option for acute myeloid leukemia (AML). However, some important questions remain related to its efficacy and safety, specifically when administered to various age cohorts among pediatric and adult patients.AimThis study aimed to investigate the efficacy of HSCT in treating pediatric patients compared to adult patients diagnosed with AML.MethodsA systematic search was conducted in PubMed, Scopus, Google Scholar, and Medline for studies published in the English language from inception to 2023. The findings were reported using the PRISMA checklist. Statistical analysis was conducted using Cochrane's software (Rev Man) version 5.4, which used random and fixed effect models when necessary.ResultsIn total, 14 studies met the criteria for meta-analysis. The results indicated a slightly positive trend in overall survival in the pediatric and combined pediatric–adult groups compared to adults alone, although the differences were not statistically significant. For relapse rate, no significant differences were observed in the adult and pediatric groups individually, while the combined pediatric–adult group showed a substantial benefit from HSCT (OR: 2.3, P-value: −0.05). A similar trend was observed in disease-free survival, where the combined group showed a modest, though not statistically significant, improvement with HSCT. Furthermore, regarding treatment-related mortality, a statistically protective effect of HSCT was observed in the adult group (OR: 0.26, P = 0.0005), while the pediatric and combined groups did not show significant effects. For graft-vs.-host disease, a significant association with HSCT was found in the pediatric group (OR: 2.58, P = 0.03), while the adult and combined groups showed no significant effects.ConclusionOur analysis showed mixed results, showing a slightly better effect of HSCT in treating pediatric patients diagnosed with AML compared to adult patients.